Comparative analysis of equipment performance in nuclear medicine - Vitor Moura de Paula; Lidia Vasconcellos de Sá; Delson Braz (Brazilian Journal of Radiation Sciences, 2020)
To ensure satisfactory equipment performance, image reliability and accurate diagnosis a set of measurements and analysis named as quality control (QC) has to be established. QC is a routine practice where the essential quipment performance  or procedure is evaluated by comparing the results to a predefined acceptable range. Currently there are 448 Nuclear Medicine Services (NMS) in Brazil that have to comply with the standards and regulations stablished by Brazilian regulatory agencies the National Nuclear Energy Commission (CNEN) and the National Health Surveillance Agency (ANVISA). Both regualtory bodies have power to control and ensure compliance with their national regulations including quality control tests of equipments to be fulfilled by all NMS operating in Brazil. However, these standards do not establish minimum performance requirements for the most tests and do not guarantee the quality to the population health care. This paper aims to evaluate and analyze the performance limits of the quality control tests in nuclear medicine practice requested in Brazilian standards and compare them with available requirements addressed in international recommendations. Regarding performance limit evaluation many of the requested tests do not address a methodology or minimum performance values to ensure what is considered satisfactory in a quality control test.  It was found that Brazilian NMS standards need revision when compared to international recommendations.